Database and Statistical Analysis: Light dependence in the phototrophy-phagotrophy balance of constitutive and non-constitutive mixotrophic protists - Schenone, Luca (2021)
Supplementary Material for the paper: Light dependence in the phototrophy-phagotrophy balance of constitutive and non-constitutive mixotrophic protists The authors are: Luca Schenone, Esteban Balseiro and Beatriz Modenutti. It contains: -A database (.xls) including all phototrophy and phagotrophy data of mixotrophic protists obtained from previous published works of primary production and bacterivory experiments. -A R script with the data analysis (modelling, error functions and plotting).